Hydrogel‐Based Slow Release of a Receptor‐Binding Domain Subunit Vaccine Elicits Neutralizing Antibody Responses Against SARS‐CoV‐2. Issue 51 (14th October 2021) - Gale, Emily C.; Powell, Abigail E.; Roth, Gillie A.; Meany, Emily L.; Yan, Jerry; Ou, Ben S.; Grosskopf, Abigail K.; Adamska, Julia; Picece, Vittoria C. T. M.; d'Aquino, Andrea I.; Pulendran, Bali; Kim, Peter S.; et al.
Abstract: The development of effective vaccines that can be rapidly manufactured and distributed worldwide is necessary to mitigate the devastating health and economic impacts of pandemics like COVID‐19. The receptor‐binding domain (RBD) of the SARS‐CoV‐2 spike protein, which mediates host cell entry of the virus, is an appealing antigen for subunit vaccines because it is efficient to manufacture, highly stable, and a target for neutralizing antibodies. Unfortunately, RBD is poorly immunogenic. While most subunit vaccines are commonly formulated with adjuvants to enhance their immunogenicity, clinically‐relevant adjuvants Alum, AddaVax, and CpG/Alum are found unable to elicit neutralizing responses following a prime‐boost immunization. Here, it has been shown that sustained delivery of an RBD subunit vaccine comprising CpG/Alum adjuvant in an injectable polymer‐nanoparticle (PNP) hydrogel elicited potent anti‐RBD and anti‐spike antibody titers, providing broader protection against SARS‐CoV‐2 variants of concern compared to bolus administration of the same vaccine and vaccines comprising other clinically‐relevant adjuvant systems. Notably, a SARS‐CoV‐2 spike‐pseudotyped lentivirus neutralization assay revealed that hydrogel‐based vaccines elicited potent neutralizing responses when bolus vaccines did not. Together, these results suggest that slow delivery of RBD subunit vaccines with PNP hydrogels can significantly enhance the immunogenicity of RBD and induce neutralizing humoral immunity. Abstract : An injectable hydrogel‐based COVID‐19 vaccine is developed using the receptor‐binding domain (RBD) antigen of the SARS‐CoV‐2 virus and clinically de‐risked adjuvants. Sustained delivery of the subunit vaccine containing a CpG/Alum complex as an adjuvant from this hydrogel depot increases titers, provides broader protection against spike variants, and leads to more robust neutralization compared to a dose‐matched bolus control.